An Improved Field Test for Rapid Estimation of Total Iron in Drinking Water - Bhutra, M.K.; Soni, Ambica (Asian Journal of Chemistry, 2010)
The present work discusses the use of bathophenanthroline reagent (in thioglycolic acid) for estimation of total iron. Instant development of light pink to reddish pink colour indicates presence of iron above 0.3 mg/L. The intensity of colour is proportional to the concentration of iron. However, exact concentration of iron can be determined from the colour chart provided therein. Naturally occurring ions present in ground waters do not interfere. The proposed test is quantitative, rapid, sensitive and easy, hence it can be incorporated in the existing water testing field kits.